System Dynamics Modeling to Improve Islamic Economic and Financial Literacy in Sharia Business Unit - Ahmad, Habib Sadewo; Santoso, Sugeng (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This study aims to identify and analyze optimal strategies that can be implemented by PT. XYZ to improve Islamic economic and financial literacy through a system dynamics modeling approach. Methodology/approach – A case study approach was applied to PT. XYZ (Sharia Business Unit) using a mixed-method qualitative and quantitative design. Primary data were obtained through surveys and in-depth interviews, while secondary data came from official reports and the national sharia literacy strategy document. The system dynamics model was developed using Vensim software. Findings – There is a 30.5% literacy gap between employees and customers. Simulation results indicate that simultaneous interventions involving employee training, digital information access, and National Sharia Board (DSN) socialization can increase employee literacy to approximately 70% and customer literacy to approximately 50% within five years. Novelty/value – This research integrates a system dynamics approach to formulate Islamic financial literacy strategies, which is still rarely applied in Indonesia's Islamic financial ecosystem.